تغير قيمة العملة والآثار المترتبة عليه - د. أيوب جمعة أحمد الجربي, (Sharwes Scientific Journal, 2025)
The issue of changing the value of currency was addressed by ancient jurists according to the situation in their time, so their statements differed and their evidence varied. This change was simple and did not pose a great danger to the economy at that time, because they relied primarily on gold and silver, which are often characterized by stability. Today, however, the issue of changing the value of money has become a great danger to the economy, because banknotes are not characterized by stability, but by change, and this is what makes the problem of changing the value of banknotes difficult. In this research, we have tried to clarify the opinion of the wise legislator in this matter in order to settle the subject of controversy, even though this issue is one of the branches that accept disagreement, and the disagreement of our jurists in the branches is a commendable matter, and it is for facilitation and not for difficulty, so what causes hardship today, may be a sign of facilitation tomorrow, and what is not suitable for a place today, and what is a cause of hardship and difficulty in one place, may be a cause of ease and prosperity in another place. We have explained in this research that repayment of the debt is in kind and not in value, and this is the principle in repayment of the debt, but if there is a change in the value of the debt, then repayment is in kind and not in value as well, if the change in value is slight, but if the change in value is excessive, then the jurists have two opinions in this case: The first: repayment is also in kind, so that we do not fall into usury, the second: repayment is in value so that neither the creditor nor the debtor is wronged.